2013
DOI: 10.1128/iai.01301-12
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Innate Response to Infective Filariae by Human Langerhans Cells Suggests a Strategy of Immune Evasion

Abstract: bFilarial infection is initiated by mosquito-derived third-stage larvae (L3) deposited on the skin that transit through the epidermis, which contains Langerhans cells (LC) and keratinocytes (KC), among other cells. This earliest interaction between L3 and the LC likely conditions the priming of the immune system to the parasite. To determine the nature of this interaction, human LC (langerin ؉ E-cadherin ؉ CD1a ؉ ) were generated in vitro and exposed to live L3. LC exposed to live L3 for 48 h showed no alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…The lack of specificity at later time points of infection could arise either because of the migration of developing larvae away from the site of infection or, alternatively, it could reflect the suppression of immune responses, a well-documented characteristic of lymphatic filarial nematodes [24,25,26]. Studies in the only fully permissive rodent host of Brugia species, the Mongolian jird, demonstrated that L3 rapidly migrated from the site of injection in the hind limb to the lymphatic system, with the majority of developing adults establishing in the lymphatics of the spermatic cord [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of specificity at later time points of infection could arise either because of the migration of developing larvae away from the site of infection or, alternatively, it could reflect the suppression of immune responses, a well-documented characteristic of lymphatic filarial nematodes [24,25,26]. Studies in the only fully permissive rodent host of Brugia species, the Mongolian jird, demonstrated that L3 rapidly migrated from the site of injection in the hind limb to the lymphatic system, with the majority of developing adults establishing in the lymphatics of the spermatic cord [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Whether L3 has a similar effect on skin resident ILC subsets remains unclear. However, these previous studies do demonstrate that L3 fails to induce ILC stimulating cytokines such as IL‐1β, IL‐18, IL‐12p40 or TSLP, alarmins IL‐25 and IL‐33 were not evaluated. The activation of cutaneous ILCs by LC is further hampered by the spatial disparity between ILCs (found predominately in the upper dermal layer) and LC (in the epidermal layer) in normal skin.…”
Section: Innate Immune Response During Filarial Infectionsmentioning
confidence: 93%
“…The response of skin resident cells such as Langerhans cells (LC), keratinocytes and dendritic cells (DC) to the invading L3 stage of B. malayi can be best described as quiescent demonstrating that filarial parasites can evade the immune response in the cutaneous tissue. Whether L3 has a similar effect on skin resident ILC subsets remains unclear.…”
Section: Innate Immune Response During Filarial Infectionsmentioning
confidence: 99%
“…These include dampening of the host's proinflammatory cytokine response, attenuating the functions of innate immune cells; generating regulatory T cells; and impairing the activation, maturation, and functions of host dendritic cells (DCs), leading to their functional impairment (2)(3)(4)(5)(6)(7)(8)(9). Impairment of host Langerhans cells has also been reported during lymphatic filarial infections, which suggests that parasites not only interfere with the functions of Langerhans cells, but have also developed means to expertly evade antigen (Ag)-presenting cell (APC) detection in the host skin (1,10). We recently documented the role of lung eosinophils and functional impairment of lung macrophages during filarial manifestation of tropical pulmonary eosinophilia (TPE) (11).…”
mentioning
confidence: 99%
“…arasites have evolved many diverse and novel strategies to evade the host immune response (1). These include dampening of the host's proinflammatory cytokine response, attenuating the functions of innate immune cells; generating regulatory T cells; and impairing the activation, maturation, and functions of host dendritic cells (DCs), leading to their functional impairment (2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%